PRAGMATIC AND STYLISTIC ASPECTS OF NEOLOGISMS IN CONTEMPORARY MEDIA AND THEIR IMPLICATIONS FOR VOCABULARY TEACHING (Journal of Universal Science Research, 2025)
This article examines the pragmatic and stylistic aspects of neologisms in modern English, with a particular focus on their presence in media materials and their role in vocabulary instruction. By analyzing neologisms found in various media sources, including online news, social media, and digital entertainment, the study identifies key word-formation processes and explores their communicative functions. The research highlights how neologisms serve to reflect cultural trends, engage audiences, and enrich language expression. In addition, the article discusses the pedagogical implications of integrating neologisms into language teaching, demonstrating their potential to enhance student engagement and vocabulary acquisition. The findings suggest that neologisms not only provide valuable insights into the evolution of the English language but also offer a practical approach to modern language instruction. The study concludes with recommendations for future research into the long-term impact of teaching neologisms and their adaptation across different educational settings